Analisis Tumbuh Kembang Balita Dengan Kehadiran Ibu Keposyandu Didesa Ragang Kec. Waru Pamekasan - Rohimah, Rohimah; Reffita, Lea Ingne (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
An integrated posyandu is a basic social and family service activity in the aspect of monitoring children's growth and development. Family activity in each posyandu activity will certainly affect the health condition of their children under five, because one of the goals of posyandu is to monitor the improvement in the nutritional status of the community, especially children under five and pregnant women. The aim of this research is to analyze the growth and development of toddlers with the mother's presence at the posyandu. The research design used is analytic with a cross sectional approach. The population and sample in this study were parents who had babies with a sample size of 55 respondents. Sampling in this study used the Probability Sampling technique with the Total Sampling technique. The data collection uses a questionnaire which is processed using the Chi square test. Based on the Chi square statistical test with the help of SPSS software with a significant level of 0.05, a value of 0.012 was obtained with a significant value of 0.000. Because the sign value is 0.044 <0.05, there is a relationship. It was concluded that the sampling in this study used a probability sampling technique with a total sampling technique, where there was a relationship between the growth and development of toddlers and the presence of mothers at the posyandu.